2015
DOI: 10.4236/ijcm.2015.61010
|View full text |Cite
|
Sign up to set email alerts
|

An Experience of Short-Term Results of Laparoscopic Inguinal Hernioplasty Using 3D Mesh in a Developing Country

Abstract: Background: The experience of short term results of laparoscopic inguinal hernia repair using 3D mesh in a developing country is reviewed. Methods: From January 2012 to February 2014, 53 patients underwent laparoscopic inguinal hernioplasty. A retrospective case series of 53 consecutive patients undergoing TEP/TAPP by a single surgical team was followed prospectively with a focused physical examination and interview. 4 out of 53 patients had recurrent hernia following open repairs and 49 had primary hernias. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 13 publications
(16 reference statements)
3
8
0
Order By: Relevance
“…Such alternatives, however, would require further investigation to ensure that reduced fixation does not come at the expense of increased recurrence. 21,30 In the present study authors have found a higher recurrence rate at 18 months in both groups with a recurrence rate of 3.3% in 3D mesh and 6.7% in polypropylene mesh. The difference in present study failed to reach any statistical significance (p-value-1.00), however it needs further investigation.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…Such alternatives, however, would require further investigation to ensure that reduced fixation does not come at the expense of increased recurrence. 21,30 In the present study authors have found a higher recurrence rate at 18 months in both groups with a recurrence rate of 3.3% in 3D mesh and 6.7% in polypropylene mesh. The difference in present study failed to reach any statistical significance (p-value-1.00), however it needs further investigation.…”
Section: Discussionsupporting
confidence: 51%
“…20 Mir I.S et al, in their study of 3D mesh in laparoscopic inguinal hernia reported immediate severe postoperative pain rate of 1.88%. 21 The reduced postoperative pain in case of 3D mesh is supported by the fact that the use of 3D mesh eliminates the use of sutures or tacks as is needed with the flat mesh thereby avoiding nerve entrapment. 22 However an increased incidence of immediate severe postoperative pain with the use of 3D mesh in present study can be attributed to small cohort and lack of extensive research data.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations